1982
DOI: 10.1007/bf00547568
|View full text |Cite
|
Sign up to set email alerts
|

Plasma high-density lipoproteins and hepatic microsomal enzyme induction

Abstract: The relationship between high-density lipoproteins (HDL) in plasma and hepatic structure and microsomal function has been investigated in 54 patients undergoing diagnostic liver biopsy. Plasma HDL cholesterol and major apoproteins were correlated with hepatic histology and microsomal enzyme activity assessed directly as liver cytochrome P-450 concentration and indirectly by plasma antipyrine clearance rate. HDL cholesterol, the concentrations of apoproteins A-I and A-II, the HDL cholesterol/total cholesterol r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 54 publications
(5 reference statements)
2
27
0
Order By: Relevance
“…Clinical studies originating from the late 1970s associated microsomal induction with parallel increases in liver protein and phospholipid and serum apolipoprotein A-I and high density lipoprotein concentrations (Luoma 1979(Luoma & 1988Luoma et al 1979aLuoma et al , 1982aLuoma et al & 1983. They also suggested that induction stimulates the synthesis of apolipoprotein A-I and high density lipoprotein apolipoprotein-phospholipid complexes, causes an atherogenic change in the serum lipo-protein profile and can thus be exploited to treat atherosclerosis in humans.…”
Section: Microsomal Induction -Gene Activation and Lipids And Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical studies originating from the late 1970s associated microsomal induction with parallel increases in liver protein and phospholipid and serum apolipoprotein A-I and high density lipoprotein concentrations (Luoma 1979(Luoma & 1988Luoma et al 1979aLuoma et al , 1982aLuoma et al & 1983. They also suggested that induction stimulates the synthesis of apolipoprotein A-I and high density lipoprotein apolipoprotein-phospholipid complexes, causes an atherogenic change in the serum lipo-protein profile and can thus be exploited to treat atherosclerosis in humans.…”
Section: Microsomal Induction -Gene Activation and Lipids And Proteinsmentioning
confidence: 99%
“…Phenytoin treatment has been associated with elevated serum high density lipoprotein cholesterol and apolipoprotein A-I levels (Nikkila et al 1978;Luoma et al 1979b) and apolipoprotein A-I/A-I1 ratios (Luoma 1988). It may increase total cholesterol at the beginning of the therapy, but after a long period of treatment low or normal cholesterol and low density lipoprotein cholesterol levels have been observed (Fears 1986).…”
Section: Anticon Vulsuntsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect on HDL metabolism is probably explained by two mechanisms, increased lipolysis of triglyceride-rich lipoproteins and induction of apolipoprotein synthesis in the liver. 87 Coffee Early epidemiological studies showed variable association between coffee and serum cholesterol concentrations and this led to the suggestion that these inconsistencies were due to differences in brewing methods." Most studies comparing caffeinated with decaffeinated coffee have shown no differences in concentrations of serum total and HDL-cholesterol, apoAI,89-91 apoB,89,91 or triglycerides.…”
Section: Intra-individual Variation In Lipids 267mentioning
confidence: 99%
“…It has been suggested that the effect of phenobarbitone and phenytoin in raising HDL-cholesterol (Durrington, 1979;Nikkila et al, 1978) is also due to enzyme induction. In patients receiving these enzyme inducers plasma HDL concentrations are proportional to the magnitude of the induction assessed directly by liver cytochrome P-450 content and indirectly by plasma antipyrine clearance rate (Luoma et al, 1982). Rifampicin is the most potent enzyme inducer in man (Ohnhaus & Park, 1979) in routine clinical use.…”
Section: Introductionmentioning
confidence: 99%